Arabic Slang Language Use in Pesantren: An Interpretive Case Study - Batmang Batmang (Institut Agama Islam Negeri (IAIN) Kendari, 2022)
Although research on the use of slang language has been widely studied, there is a paucity of studies that specifically looks at Arabic slang language among santri community in Indonesia. To fill such a void, the present study aims at examining the use of Arabic slang language among santri community in a modern pesantren in Southeast Sulawesi Province, Indonesia, and the factors that influence the use of such a language. Nested in an interpretive case study with data analyzed using Allan and Burridge’s (2006) slang language framework, the findings of this study suggest emerging types of slang used among the santri, which are in the forms of overlapping, clipping, acronyms, word-for-word translation, and the addition of local enclise elements. Such a language use was exclusively influenced by habits, creativity, and simplification in communication. Implications of the study show that the use of certain Arabic vocabulary can signal how a foreign language is acquired outside of the class